Effective representation and the role of coalitions within the IMF - Ngaire Woods; Domenico Lombardi (University of Oxford, Global Economic Governance Programme (GEG), 2005)
The IMF is governed by a 24-member Executive Board, which represents 184 countries. Although often prized as a small and efficient decision-making body, the Board represents some countries more effectively than others. This is due to the institutional structure and incentives within which the Board operates. Prime among them is a system of constituencies, which have formed and evolved as countries have sought to improve their position in the organization. These groups vary in size, shared interests, and distribution of power. Their effectiveness is not only affected by these attributes. It is also determined by decision-making rules across the institution, by the lack of formal accountability of Board members, and by the strength of other coalitions of countries acting informally within the institution. The analysis implies that representation on the IMF Board could be improved without altering the size of the Board.
Keywords: 330